Obtention and characterization of rapeseed protein isolates. - N. Gonçalves; J. Vioque; A. Clemente; R. Sánchez-Vioque; J. Bautista; F. Millán (Grasas y Aceites, 1997)
A method for the obtention of protein isolates from defatted rapeseed flour has been designed. The process includes a basic extraction followed by a precipitation at the isoelectric point of the proteins. The precipitate is washed with water (pH 4.5), ethanol and acetone, obtaining a protein isolate with 86% of protein and reducing the contents in polyphenols and soluble sugars in more than 90% with respect to the defatted flour. The final product have physico-chemical characteristics that make it atractive to be used as food and for the obtention of protein hydrolizates.